Penggunaan Phet Colorado untuk Melatih Keterampilan Proses Sains pada Materi Bentuk Molekul: Penelitian - Annisa Sholehah Ayu Febriyanti; Muntholib; Dasianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to train the science process skills of students in class X-4 SMA Brawijaya Smart School through the use of PhET Colorado simulation media on molecular shape material. This study was motivated by the low science process skills of students identified based on observation findings and written test results. The research was conducted using the Kurt Lewin model of classroom action method. Learning uses the